Almost Pseudo Ricci Symmetric Manifold Admitting Schouten Tensor. Issue 2 (3rd July 2021) - Ali, Mohabbat; Vasiulla, Mohd
Abstract: The object of the present paper is to study almost pseudo Ricci symmetric manifold admitting Schouten tensor and investigated some geometric properties of this manifold.